Comparison of Outcome of Teenage Pregnancy with Non- teenage pregnancy - Sharma, Deepanjali; Ghimire, Sailaja; Jha, Meena; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To analyze the maternal and fetal outcome in teenage pregnancy (≤ 19years) with that of pregnancy at optimal childbearing age group (20- 34 years). Methodology: This was a hospital based observational analytical study conducted at Paropakar Maternity and Women’s Hospital in Kathmandu from August 2016 to February 2017.Results were analyzed using SPSS 21 taking p-value≤ 0.05 as statistically significant. Results: There were 200 cases in each group (≤19 and 20-34 years). Anemia (p=0.001), hypertensive disorder of pregnancy (p=0.001), preterm delivery (p=0.001), Cesarean Section rate (p=0.006), 5-minute Apgar score (p=0.035), low birth weight (p=0.017) and neonatal admission rates (p=0.018) were significantly high in teenage pregnancy. Conclusions: Both maternal and neonatal complications are increased in teenage pregnancy in comparison to the optimal reproductive age group. Key words: complications, pregnancy, teenage